Social, Psychological, and Behavioral Predictors of Salivary Bacteria, Yeast in Caries-Free Children. (April 2022) - Kopycka-Kedzierawski, D.T.; Scott-Anne, K.; Ragusa, P.G.; Cvetanovska, M.; Flint, K.; Feng, C.; Watson, G.E.; Wong, C.L.; Billings, R.J.; Quivey, R.J.; O'Connor, T.G.
Introduction: Early childhood caries (ECC) is a complex, multifactorial oral disease that is a major public health concern because it is prevalent, profoundly alters a child's quality of life, is difficult to treat effectively, and has a distressing tendency to recur following treatment. Objectives: The purpose of the study was to examine social, psychological, and behavioral predictors of salivary bacteria and yeast in young children at risk for ECC. Methods: A sample of 189 initially caries-free preschool children was assessed for child stress physiology from salivary cortisol, child and family stress exposure, diet, oral health behaviors, and sociodemographic risks. Multiple logistic regression analysis was implemented to examine the associations between these risk factors and cariogenic microorganisms: mutans streptococci (MS), lactobacilli (LB), and Candida species. Results: Higher baseline salivary cortisol (odds ratio [OR] = 6.26; 95% confidence level [CL], 1.69–23.16) and a blunted response to an acute laboratory stressor (OR = .56; 95% CL, .37–.83) were associated with an increased likelihood of elevated salivary MS (≥10 5 colony-forming units/mL) in caries-free children. Sociodemographic risk for cariogenic microorganisms was also found. Specifically, lower education attainment of the parent/primary caregiver was associated with children being more likely to carry salivary Candida species and elevated salivary MS; in addition, children from households with an unemployed parent/primary caregiver were more likely (OR = 3.13; 95% CL, 1.2–8.05) to carry salivary Candida species and more likely (OR = 3.03; 95% CL, 1.25–7.33) to carry elevated levels of MS and/or salivary Candida and/or LB. Conclusions: The impact of sociodemographic risk and stress physiology on cariogenic disease processes are evident prior to ECC onset. The findings provide novel data on the early onset of cariogenic processes in children and the importance of considering sociodemographic, psychosocial, and behavioral factors when judging ECC risk. Knowledge Transfer Statement: The findings provide valuable and novel findings that, pre-ECC onset, the caries disease process is explicable from a detailed assessment of behavioral, sociodemographic, and psychosocial stress variables.